3D channel emulation in multi‐probe setup. Issue 9 (1st April 2013) - Fan, W.; Sun, F.; Kyösti, P.; Nielsen, J.; Carreño, X.; Knudsen, M.; Pedersen, G.
Abstract : A technique to emulate 3D geometry‐based channel models in a multi‐probe over the air test setup is presented. The proposed technique provides a general emulation framework for any spherical incoming power spectrum. The emulation method results in two optimisation objectives, which are both convex. They give optimal emulation accuracy and allow relatively low computational complexity.